Borrelial lymphocytoma in a child - Sylwia Feszak; Igor Feszak; Radosław Opiła; Jarosław Peregud-Pogorzelski (Termedia Publishing House, 2022)
Borrelial lymphocytoma (BL) is a rare manifestation of Lyme disease characterized by pathological lymphoproliferation on the skin (a type of cutaneous pseudolymphoma) in reaction to a Borrelia infection. It usually manifests itself as red plaques or swollen nodules, most commonly located on the ear lobes, genitals, or around the nipples. We describe a case of a 5-year-old girl with a painful erythematous nodule of the right auricle. The initial symptomatic treatment (with antihistamines and topical anti-inflammatory agents) resulted in temporary partial relief. There was a history of tick bites 3 and 5 months prior to the first manifestation of the disease. A positive serology test result for Borrelia burgdorferi (both chemiluminescent immunoassay and Western-Blot) led to the diagnosis of BL. The administration of an oral antibiotic therapy resulted in the quick disappearance of the lesion.